Concrete power generation device using conductive hot melt and its manufacturing method
The conductive hot melt layer in power generation devices addresses the instability of hydrogel electrodes by ensuring stable adhesion and conductivity, enabling long-term power generation on structures like concrete.
Patent Information
- Application Number
- JP2020211850
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-12-21
AI Technical Summary
Existing power generation devices using hydrogel electrodes face instability due to changes in water content with humidity and temperature, leading to reduced conductivity and adhesiveness, making long-term power generation challenging.
A power generation device utilizing a conductive hot melt layer composed of a conductive filler and thermoplastic resin, which is adhered to structures like concrete or mortar, providing stable adhesion and conductivity over time.
The conductive hot melt layer ensures stable power generation over a long period by maintaining adhesion and conductivity, despite environmental changes.
Smart Images

Figure 0007604876000003 
Figure 0007604876000001 
Figure 0007604876000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a concrete power generation device that can form a battery in a state where it is easily and firmly attached to a structure containing an electrolyte, such as a material such as stone, stainless steel, concrete, mortar, skin, or wood, and a method for manufacturing the same. [Background technology]
[0002] By installing sensors in infrastructure structures such as concrete and remotely monitoring them at all times, the state of the infrastructure structures can be accurately grasped. In addition, since there is a demand for the construction of a monitoring system using sensors that enables efficient maintenance and management, it is necessary to develop an energy harvesting device that enables long-term operation of the sensors. Usually, power generation by forming a battery using an electrolyte structure such as concrete is made possible by installing a conductive hydrogel electrode containing an electrolyte aqueous solution on the surface of the structure (Patent Document 1, Patent Document 2). However, depending on the environment in which the structure is placed, the water content of the hydrogel also changes according to the humidity and temperature, so that the conductivity and adhesiveness of the hydrogel are reduced, and it is expected that it is unsuitable for long-term stable power generation. On the other hand, Patent Document 3 discloses an electrode sheet made of a conductive hot melt layer that does not contain water. In Patent Document 3, the conductive hot melt layer made of a thermoplastic resin and a conductive filler is attached to a structure, and further heated and compressed, making it possible to stably acquire electrical signals from the structure for a long period of time and maintain adhesiveness. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-003977 A [Patent Document 2] JP 2020-113379 A [Patent Document 3] JP 2020-064037 A Summary of the Invention [Problem to be solved by the invention]
[0004] The adhesive gel sheet of Patent Document 1 is made by processing a hydrogel containing water, and has a problem that the power generation performance changes depending on the degree of drying of the adhesive gel sheet, and furthermore, it is expected that it is unsuitable for long-term power generation because there is a risk of the adhesiveness decreasing due to swelling. The present invention has been made in consideration of such a situation, and aims to provide a concrete power generation device capable of long-term power generation. [Means for solving the problem]
[0005] As a result of intensive research into solving the above problems, the inventors discovered that long-term power generation is possible by using a power generation device having a conductive hot melt layer as described below, and thus completed the present invention.
[0006] That is, the present invention relates to a power generation device comprising a structure having an electrolyte and a pair of electrodes arranged on the structure, in which at least one of the pair of electrodes has a conductive hot melt layer containing a conductive filler and a thermoplastic resin.
[0007] The present invention also relates to a power generating device, wherein the structure having the electrolyte is concrete or mortar.
[0008] The present invention also relates to a power generating device, wherein the conductive filler includes at least one selected from the group consisting of graphite, carbon black, carbon nanotubes, graphene, graphene oxide, silver, copper, tin, zinc, zinc oxide, nickel, manganese, aluminum, and ITO.
[0009] The present invention also relates to a power generating device, wherein the conductive filler includes graphite, carbon black, carbon nanotubes, graphene, or graphene oxide.
[0010] The present invention also relates to a power generating device, in which the thermoplastic resin includes a thermoplastic elastomer.
[0011] The present invention relates to a power generating device, in which the conductive hot melt layer is disposed in a pattern on a sheet-like substrate.
[0012] The present invention also relates to a method for manufacturing a power generation device comprising a structure having an electrolyte and a pair of electrodes arranged on the structure, characterized in that at least one of the pair of electrodes has a conductive hot-melt adhesive layer containing a conductive filler and a thermoplastic resin, and the method for manufacturing the power generation device comprises a step of adhering the conductive hot-melt adhesive layer to a surface of the structure.
[0013] The present invention also relates to a method for manufacturing a power generation device, characterized in that the step of adhering the conductive hot melt adhesive layer to a surface of a structure includes a step of heating the conductive hot melt adhesive layer to adhere to the surface of a structure. Effect of the Invention
[0014] According to the present invention, it is possible to fabricate a concrete power generation device capable of supplying a stable power supply for a long period of time. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 shows an example of the configuration of a power generating device in which a conductive hot melt adhesive layer used in the present invention and a structure are laminated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited to the embodiments described below, and various modifications are possible without departing from the spirit of the present invention.
[0017] The power generation device of the present invention is a power generation device comprising a structure having an electrolyte and a pair of electrodes arranged on the structure, characterized in that at least one of the pair of electrodes has a conductive hot melt layer containing a conductive filler and a thermoplastic resin.
[0018] <Conductive filler> Examples of the conductive filler used in the present invention include metals such as silver, gold, copper, nickel, zinc, manganese, iron, tin, cobalt, and aluminum, and alloys thereof; metal oxides such as zinc oxide, tin oxide-doped indium oxide (ITO), tin oxide-doped indium oxide (FTO), tin oxide (IO), neodymium-barium-indium oxide, and indium zinc oxide (IZO); organic substances such as polythiophenes, polypyrroles, polyanilines, and oligothiophenes; inorganic insulators such as alumina and glass, and polymers such as polyethylene and polystyrene, whose surfaces are coated with a conductive substance; and carbon-based substances such as carbon black, graphite, graphene, graphite, carbon nanotubes, fullerenes, graphene oxide, and acetylene black, but are not limited to these. Also, preferred are graphite, carbon black, carbon nanotubes, graphene, graphene oxide, silver, copper, tin, zinc, zinc oxide, nickel, manganese, and ITO, and more preferred are graphite, carbon black, carbon nanotubes, graphene, and graphene oxide. These may be used alone or in combination of two or more. These fillers may also have a structure in which two or more types of layers are connected together by coating or the like. The conductive filler is preferably carbon-based because it has excellent resistance to various types such as heat resistance, water resistance, and acid resistance. Also, since the conductive filler is dispersed in the thermoplastic resin, it is retained in the conductive hot melt adhesive layer without dissociating and penetrating into the structure.
[0019] The shape of the conductive filler may be, but is not limited to, flake (scale), spherical, needle-like, fibrous, or dendritic. If it is desired to reduce the amount of conductive filler added in order to strengthen the adhesive strength, flake (scale) filler and a mixture of flake (scale) filler and other conductive filler are preferred.
[0020] The content ratio of the conductive filler in the entire conductive hot melt adhesive layer is not particularly limited, but for carbon-based fillers such as carbon black and graphite, it is preferably 10 to 80% by weight, more preferably 20 to 70% by weight, and even more preferably 25 to 60% by weight, from the viewpoint of conductivity and adhesive strength. If it is less than 10% by weight, the conductivity may be insufficient, and if it exceeds 80% by weight, the adhesive strength may be insufficient. On the other hand, for metal fillers such as silver and copper, it is preferably 40 to 80% by weight, more preferably 50 to 70% by weight. If it is less than 40% by weight, the conductivity may be insufficient, and if it exceeds 80% by weight, the adhesive strength may be insufficient.
[0021] <Thermoplastic resin> The thermoplastic resin may be a so-called hot melt resin, which is a non-curable resin that becomes flowable at high temperatures and returns to a non-flowable state upon cooling, or a curable resin, which undergoes a curing (crosslinking) reaction after the thermoplastic resin is applied to a substrate.
[0022] The thermoplastic resin preferably contains at least one selected from the group consisting of thermoplastic resins including polyurethane, acrylonitrile, diene, acrylic, butadiene, polyamide, polyvinyl butyral, olefin, isoprene, butadiene, chloroprene, acrylonitrile, polyester, polyvinyl chloride, styrene, phenoxy, ethylene-vinyl acetate, fluorine, silicone, and copolymers thereof, but is not limited to these resins. From the viewpoints of durability, weather resistance, heat resistance, and adhesive strength, it is more preferable that the thermoplastic resin contains a styrene-based thermoplastic resin. The thermoplastic resin may be used alone or in combination of two or more types. Furthermore, the thermoplastic resin may be a copolymer formed by linking different monomers.
[0023] Styrene-based thermoplastic resins, specifically styrene-based elastomers, generally have polystyrene blocks and rubber intermediate blocks, with the polystyrene portion forming physical crosslinks (domains) and becoming crosslinking points, and the intermediate rubber block giving the product rubber elasticity. The intermediate soft segments include polybutadiene (B), polyisoprene (I) and polyolefin elastomers (ethylene-propylene, EP), and are divided into linear (linear type) and radial (radical type) depending on the arrangement with the hard segment polystyrene (S). Among the above-mentioned preferred styrene-based elastomers, the present invention may more specifically include at least one selected from the group consisting of styrene-isoprene-styrene block copolymer (SIS), hydrogenated styrene-ethylene-butylene-styrene block copolymer (SEPS), styrene-butylene-styrene block copolymer (SBS), hydrogenated styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-butadiene-isoprene-styrene block copolymer (SBIS) and hydrogenated styrene-butadiene-isoprene-styrene block copolymer (SEEPS), but is not limited to these resins.
[0024] The conductive hot melt adhesive layer may contain various additives such as tackifiers, softeners, antioxidants, and other additives as appropriate, provided that the effects of the present invention are not impaired.
[0025] <Tackifier> Examples of tackifiers include terpene resins, hydrogenated terpene resins, rosin resins, hydrogenated rosin resins, hydrocarbon resins, hydrogenated hydrocarbon resins, epoxy resins, hydrogenated epoxy resins, ketone resins, hydrogenated ketone resins, polyamide resins, hydrogenated polyamide resins, elastomer resins, hydrogenated elastomer resins, phenol resins, hydrogenated phenol resins, petroleum resins, hydrogenated petroleum resins, styrene resins, and hydrogenated styrene resins. These tackifier resins can be used alone or in combination. Among these, hydrogenated hydrocarbon resins are preferred from the viewpoint of durability. Hydrogenation eliminates the conjugated double bonds in the molecular structure, so that the conductive hot melt adhesive layer containing the tackifier is less susceptible to deterioration due to light or heat when permanently bonded to a structure, making it possible to maintain adhesive strength for 10 years or more.
[0026] <Softener> Examples of the softener include petrolatum, mineral oil, vegetable oil, and animal oil. Examples of the mineral oil include liquid paraffin, paraffin, paraffin-based mineral oil in which the number of carbon atoms in the paraffin chain accounts for 50% or more of the total number of carbon atoms, naphthenic mineral oil in which the number of carbon atoms in the naphthenic ring accounts for 30 to 40% by weight of the total number of carbon atoms, and aromatic mineral oil in which the number of aromatic carbon atoms accounts for 30% by weight or more of the total number of carbon atoms. Vegetable oils and fats: Olive oil, carnauba wax, rice germ oil, corn oil, camellia oil, castor oil, jojoba seed oil, mink oil, eucalyptus leaf oil, and the like. Animal oils and fats: Beeswax, squalane, and honey. Other examples of softening agents include myristic acid, oleic acid, isopropyl myristic acid, zinc myristic acid, octyldodecyl myristate, glycerin triisooctanoate, octyldodecanol, hexyldecanol, diisopropyl adipate, diethyl sebacate, stearic acid, isostearic acid, crotamiton, medium-chain triglyceride, ethylene glycol salicylate, cetyl ethylhexanoate, glycol distearate, cetearyl alcohol, cetanol, cetyl palmitate, ethylhexyl palmitate, isopropyl palmitate, and behenyl alcohol. The softener may contain a plasticizer, and examples thereof include dioctyl phthalate, diisodecyl phthalate, bis-2-ethylhexyl phthalate, dibutyl phthalate, dicyclohexyl phthalate, diisononyl phthalate, tributyl acetylcitrate, dioctyl adipate, diisononyl adipate, tricresyl phosphate, trioctyl trimellitate, etc. These softeners may be used alone or in combination of two or more.
[0027] <Antioxidants> Examples of the antioxidant include pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, diethyl [[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, 4,6-bis(octylthiomethyl)-o-cresol, ethylene bis(oxyethylene) bis[3-(5-t-butyl)-4-hydroxyphenyl]methyl]phosphonate, and the like. Examples of the phenol-based antioxidant include pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, etc. The phenol-based antioxidant is preferably pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], and the phosphorus-based antioxidant is preferably tris(2,4-di-t-butylphenyl)phosphite.
[0028] <Dispersant> The addition of a dispersant is effective for controlling the fluidity and viscosity when forming the conductive hot melt adhesive layer and the conductive layer by a printing / coating method, and is particularly effective when a solvent is used. The content of the dispersant can be appropriately selected depending on the purpose of use, but it is preferably 10 to 300% relative to the conductive filler. The dispersant used can be obtained commercially, for example, DISPERBYK-102, DISPERBYK-103, DISPERBYK-106, DISPERBYK-108, DISPERBYK-110, DISPERBYK-111, DISPERBYK-130, DISPERBYK-140, DISPERBYK-150, DISPERBYK-160, DISPERBYK-161, DISPERBYK-162, DISPERBYK-163, DISPERBYK-164, DISPERBYK-165, DISPERBYK-180, DISPERBYK-190, DISPERBYK-1 91, DISPERBYK-198, DISPERBYK-2000, DISPERBYK-2001, DISPERBYK-2010, DISPERBYK-2012, DISPERBYK-2015, DISPERBYK-2022, DISPERBYK-2055, DISPERBYK-2096, DISPERBYK-2155, DISPERBYK-2164, BYK-9076, BYK-9077, BYKOPLAST-1000, DISPERPLAST-1018, DISPERPLAST-1018, DISPERPLAST-1042, DISPERPLAST-1150, and the like, but are not limited to these.
[0029] <Other ingredients> As other components, for example, from the viewpoint of reducing the cure shrinkage rate, reducing the thermal expansion rate, improving dimensional stability, improving the elastic modulus, adjusting the viscosity, improving strength and toughness, curing agents such as polyisocyanate, epoxy resin, polycarbodiimide compound, amine-based compound, and organic or inorganic fillers can be blended. Such fillers may be composed of materials such as polymers, ceramics, metal salts, and dyes and pigments. The shape of the fillers is not particularly limited, and may be, for example, particulate or fibrous. In addition, in order to improve the leveling property with the substrate, the adjustment of the coating property during coating printing, and the adhesion property, silane coupling agents, titanate coupling agents, flame retardants, storage stabilizers, metal deactivators, ultraviolet absorbers, thixotropy imparting agents, leveling agents, dispersion stabilizers, fluidity imparting agents, defoamers, and coloring materials can also be added.
[0030] <Method for producing conductive hot melt adhesive layer> The method for producing the conductive hot melt adhesive layer used in the present invention is not particularly limited, but an example is shown below. In addition to the conductive filler, a thermoplastic resin and, if necessary, a softener, a tackifier, an antioxidant, and other optional components are mixed to form a mixture. The mixture is dispersed by a known dispersing machine to form a dispersion, but the order of mixing is not particularly limited, and a dispersion in which a thermoplastic resin, a softener, and a tackifier are dispersed in advance and a mixture of a conductive filler may be dispersed. Examples of dispersing machines include roll mills such as two-roll and three-roll, ball mills such as ball mills and vibration ball mills, paint conditioners, bead mills such as continuous disk bead mills and continuous annular bead mills, and Banbury mixers, kneaders, melting pots equipped with stirrers, and single- or twin-screw extruders. Next, these are heated and mixed in a heat melting process, or dissolved in an appropriate solvent and stirred and mixed, and then the resulting mixture is obtained through a printing and coating process described below. The conductive hot melt adhesive layer used in the present invention can be obtained by a heat melting process that does not use a solvent, from the viewpoint of the complication of the process due to the solvent removal and the associated increase in cost, and further from the viewpoint of the adverse effect on the global environment due to the use of a solvent. In addition, when the conductive hot melt adhesive layer used in the present invention contains a carbon-based filler, the fluidity is extremely reduced, so in consideration of the coatability, printability, and uniform dispersion, it is preferable to include a process using a solvent. The conductive hot melt adhesive layer used in the present invention can be used with only a conductive filler and a thermoplastic resin, but it is preferable to include a softener, a tackifier, an antioxidant, and a dispersant from the viewpoint of fluidity, adhesion, and oxidation stability. The thickness of the conductive hot melt adhesive layer used in the present invention is not particularly limited, but is preferably 10 to 500 μm, more preferably 50 to 400 μm, and even more preferably 100 to 300 μm. The conductive hot melt adhesive layer used in the present invention is disposed on the surface of a structure and used. The conductive hot melt adhesive layer used in the present invention may be directly attached to the structure, but after being attached to the surface of the structure, it can be melted by heating and solidified by cooling, so that it can be held in close contact with the surface of the structure and stably maintained.In addition, the conductive hot melt adhesive layer fills the voids on the surface of the structure, thereby suppressing the contact resistance. In addition, for ease of bonding to the structure, it is preferable that the conductive hot melt adhesive layer has adhesiveness.
[0031] The method of forming the conductive hot melt adhesive layer includes a coating / printing method on a substrate, and is not particularly limited. Coating methods include slot spray coating, omega coating, spiral coating, control seam coating, slot spray coating, dot coating, hot melt applicator coating, hot melt coater coating, blade coat coating, dip coating, gravure coat coating, curtain spray coating, bead coating, and hot melt roll coater spin coat coating, and printing methods include inkjet printing, spray printing, roll coat printing, doctor roll printing, doctor blade printing, curtain coat printing, slit coat printing, screen printing, reverse printing, transfer printing, push coat printing, and slit coater printing. Drying conditions when a solvent is used are not particularly limited, and include hot air drying, infrared rays, and reduced pressure methods. Drying conditions vary depending on the film thickness and the selected organic solvent, but typically involve hot air heating at about 60 to 200°C. The thickness of the conductive hot melt adhesive layer is preferably 10 to 500 μm. The conductive hot melt adhesive layer can also be crosslinked by heating or ultraviolet irradiation. When a substrate is not required, a conductive laminate similar to that described above may be formed using a peelable substrate, and then the substrate may be peeled off. When the conductive hot melt adhesive layer is patterned, the various printing methods described above can be used.
[0032] <Base material> The substrate for forming the conductive hot melt adhesive layer is selected from the group consisting of a resin sheet, paper, an aluminum sheet (aluminum foil), a copper foil sheet, and a zinc foil sheet. For example, the resin sheet may be a resin sheet formed from a resin such as a polyester resin such as polyethylene terephthalate (PET) or polyethylene naphthalate (PEN), a polycarbonate resin, a fluorine resin, a polyarylate resin, an acrylic resin, a polyphenylene sulfide resin, a polystyrene resin, a vinyl resin, a vinyl chloride resin, a polyimide resin, an epoxy resin, a polyimide resin, or a polyolefin resin such as polyethylene, polypropylene, or polynorbornene. In addition, the substrate may be a laminate in which a metal is laminated on these sheets, for example, a laminate in which a metal is laminated on a polyethylene terephthalate (PET) sheet. In addition, since the substrate may be deformed by heat, a substrate with high heat resistance such as a polyimide sheet, a polyethylene naphthalene sheet, a polynaphthalene sheet, a propylene sheet, a silicone resin sheet, or a fluorine resin sheet, or a substrate with improved heat resistance due to filling with a filler, is preferable. Examples of commercially available substrates include Kapton, Lumirror, Toray-DuPont Co., Ltd.'s Kapton, Lumirror, Torayfan, Torelina, and Miktron, Teijin Co., Ltd.'s Teonex, Panlite, Tetoron Film, Mylar, and Melinex, Toyobo Co., Ltd.'s Pylen, Cosmoshine, and Harden, etc.
[0033] <Electrode> The electrodes used in the present invention are disposed in a structure having an electrolyte. At least one of the pair of electrodes to be disposed has the conductive hot melt layer described above, and the other electrode may be a conductive hot melt layer or another electrode. Examples of the other electrode include a conductive tape.
[0034] <Conductive tape> The conductive tape may be any tape that has adhesiveness and conductivity, and may be a conductive tape containing conductive fillers such as copper, silver, zinc, aluminum, carbon, tin, gold, nickel, carbon, and iron, and may be a type with an electrically conductive adhesive layer on one side or a type with an electrically conductive adhesive layer on both sides. Although not particularly limited, it is preferable that the thickness of the adhesive layer is 100 um or more. Examples of commercially available conductive tapes include ZAP tape, ZAP seal, and ZAP sheet manufactured by Mitsui Sumitomo Metal Mining Co., Ltd., copper foil conductive tape 1245, copper foil conductive tape 1181, tin-plated copper foil conductive tape 1183, nickel-plated polyester cloth conductive tape 2191FR, conductive single-sided tape SC-CUN0145B, lead foil tape 420, conductive aluminum foil tape AL-25BT, and aluminum foil conductive tape 1170 manufactured by Teraoka Seisakusho. Conductive aluminum foil adhesive tape 8303, conductive copper foil adhesive tape 8323, conductive aluminum foil double-sided tape 791, etc. can be mentioned.
[0035] <Structure> Examples of structures that can be used in the power generating device of the present invention include plastic, paper, composites of paper and plastic, silver, stainless steel, copper, iron, aluminum, alloys, minerals, non-ferrous metals, concrete, mortar, slate, tiles, paving materials, skin, wood, cloth, leather, rubber, cork, glass, etc. The thickness of the structure used in the present invention is preferably 1 mm or more. The type of structure used in the present invention is not particularly limited, but concrete and mortar are preferred because they contain a large amount of electrolytes such as chloride ions, sodium ions, and calcium ions, as well as water, as described below, making it easier to obtain electrical signals from the inside. The concrete and mortar mentioned here are a mass of cement mixed with water and hardened over time. It may contain fine aggregates such as sand and coarse aggregates such as gravel. Concrete hardens by the dissolution and precipitation reaction of cement. Cement is composed of elements such as calcium, silicon, aluminum, and iron. When it comes into contact with water, calcium ions dissolve and the calcium ions in the aqueous solution increase. The main components, silicic acid (SiO2) and alumina (Al2O3), exist as stable substances (polymers) in which the ions are polymerized with each other and do not react with calcium ions. However, in cement, silicate ions and aluminum ions (alumina ions) exist as monomers that react relatively easily, and when the surrounding calcium ions are leached out, they dissolve into the solution and react with calcium ions and water molecules to form cement hydrate (CSH: ettringite), which is difficult to dissolve in water, and the remaining calcium ions precipitate as calcium hydroxide. The hydrate particles bond to each other and harden. The bonds between particles are thought to be held together by intermolecular attraction and hydrogen bonds, and unlike calcium hydroxide, CSH has fine bonds of 0.1 μm or less, and the bonding area between particles per unit volume is significantly large, so it exerts high bonding strength and exhibits strength in the hardened body. The concrete layer of the present invention can be made of cement obtained by mixing and solidifying cement and water, mortar obtained by mixing and solidifying cement, water, and fine aggregate (sand), and concrete obtained by mixing and solidifying cement, water, and aggregate (fine aggregate (sand) and coarse aggregate (gravel)).
[0036] <Power generation device and method for producing the same> The power generation device of the present invention is composed of a structure having an electrolyte and a pair of different electrodes installed on the structure, and at least one of the pair of electrodes is composed of a conductive hot melt adhesive layer. The power generation device can be manufactured by attaching a pair of different electrodes to a structure using the adhesive force of the electrodes. In addition, since the contact resistance is suppressed and the effects of noise suppression and potential stability are obtained, it is preferable to manufacture the power generation device by melting the conductive hot melt adhesive layer attached to the structure with heat using, but not limited to, an iron, a heater, a heating wire, hot air, an infrared heater, an IH heating device, etc. to bond the conductive hot melt adhesive layer to the structure. Furthermore, by installing wiring on the electrodes installed on the power generation device and electrically connecting the wiring to an electromotive force extraction unit, electromotive force can be extracted from the power generation device.
[0037] By placing different types of electrodes on the surface of a structure containing an electrolyte, it is possible to efficiently generate electromotive force. For example, a battery is formed by placing a first electrode layer and a second electrode layer made of a conductive filler with a different work function, electrode potential, redox potential, or ionization tendency on the surface of a concrete structure, and electromotive force can be efficiently generated. Here, by providing a hydrogel layer between the first electrode layer placed on the surface of the concrete structure and between the concrete structure and the second electrode layer, respectively, it is expected that the adhesion at the interface between the concrete structure and the first and second electrode layers will be improved and the contact resistance will be reduced. However, on the other hand, the amount of water contained in the hydrogel layer changes due to environmental changes over time, which makes it difficult to maintain stable adhesion and contact resistance, and the potential stability will decrease. Even when a non-volatile ionic liquid is used instead of water, if the liquid retention performance in the gel is low, the ionic liquid will penetrate into the concrete over time, and the potential stability will decrease. Therefore, in the power generating device of this embodiment, by using the conductive hot melt adhesive layer containing no moisture or solvent used in the present invention in place of the electrode layer and hydrogel layer described above, there is no need to consider the effects of changes in moisture content due to environmental fluctuations, and electromotive force can be generated semi-permanently while maintaining stable adhesion and contact.
[0038] <Resistivity> The volume resistivity of the conductive hot melt adhesive layer is set to 1×10 -1 Ω cm or more 1×10 3 It is preferable to set the volume resistivity of the conductive hot melt adhesive layer to a value less than Ω·cm. The reason for this is that if the volume resistivity of the conductive hot melt adhesive layer is within this range, a stable electromotive force can be obtained. Also, if the volume resistivity of the conductive hot melt adhesive layer is less than 1×10 0 Ω cm or more 1×10 3 A value of less than 1×10 Ω cm is preferable. 1 It is more preferable that the volume resistivity is less than Ω·cm. The detailed method for measuring the volume resistivity will be specifically described in the Examples.
[0039] <Adhesive strength> The adhesive strength value of the conductive laminate varies depending on the structure, but the preferred range is 2 N / 25 mm or more and less than 40 N / 25 mm, and more preferably 10 N / 25 mm or more and less than 30 N / 25 mm. The detailed method for measuring the adhesive strength will be specifically described in the Examples. EXAMPLES
[0040] The present invention will be described in detail below with reference to examples, but these examples are merely one embodiment of the present invention and the present invention is not limited to these examples. In the tables, "wt%" means "% by weight".
[0041] <Preparation of concrete> The concrete used in the manufacturing examples and practical examples tests was prepared using standard sand for mortar sand ISO671 testing in accordance with JISR5201. The concrete and concrete structure described hereinafter refer to the concrete prepared in this section.
[0042] [Preparation of conductive hot melt adhesive layer] <Production Example 1> Carbon filler was added to a thermoplastic resin based on SIS (styrene-isoprene-styrene) elastomer using a three-roll mill, and then tackifier, softener, antioxidant, solvent, and dispersant were added and mixed for 1 hour. The resulting mixture was printed on a Kapton substrate to obtain an electrode sheet with a thickness of 200 μm. The volume resistivity of the electrode part was 2×10 1 It was Ωcm. <Production Example 2> Carbon filler was added to a thermoplastic resin based on SIS (styrene-isoprene-styrene) elastomer using a three-roll mill, and then tackifier, softener, antioxidant, solvent, and dispersant were added and mixed for 1 hour. The resulting mixture was printed on a PEN substrate to obtain an electrode sheet with a thickness of 100 μm. The volume resistivity of the electrode part was 3×10 3 It was Ωcm.
[0043] <Production Example 3> Carbon filler was added to a thermoplastic resin based on SEPS (styrene-ethylene-propylene-styrene) elastomer using a three-roll mill, and then tackifier, softener, antioxidant, solvent, and dispersant were added and mixed for 1 hour. The resulting mixture was printed on a Kapton substrate to obtain an electrode sheet with a thickness of 1000 μm. The volume resistivity of the electrode part was 2×10 1 It was Ωcm.
[0044] <Production Example 4> Carbon filler was added to a thermoplastic resin based on polyamide resin using a three-roll mill, and then tackifier, softener, antioxidant, solvent, and dispersant were added and mixed for 1 hour. The resulting mixture was printed on a Kapton substrate to obtain an electrode sheet with a thickness of 150 μm. The volume resistivity of the electrode part was 5×10 1 It was Ωcm.
[0045] <Production Example 5> Carbon filler was added to a polyester-based thermoplastic resin using a three-roll mill, and then tackifier, softener, antioxidant, solvent, and dispersant were added and mixed for 1 hour. The resulting mixture was printed on a Kapton substrate to obtain an electrode sheet with a thickness of 500 μm. The volume resistivity of the electrode part was 4×10 1 It was Ωcm.
[0046] <Production Example 6> Carbon filler was added to a polyurethane-based thermoplastic resin using a three-roll mill, and then tackifier, softener, antioxidant, solvent, and dispersant were added and mixed for 1 hour. The resulting mixture was printed on a Kapton substrate to obtain an electrode sheet with a thickness of 400 μm. The volume resistivity of the electrode part was 2×10 1 It was Ωcm.
[0047] <Production Example 7> Silver filler was added to a thermoplastic resin based on SEPS (styrene-ethylene-propylene-styrene) elastomer using a three-roll mill, and then tackifier, softener, antioxidant, and solvent were added and mixed for 1 hour. The resulting mixture was printed on a PEN substrate to obtain an electrode sheet with a thickness of 200 μm. The volume resistivity of the electrode was 4×10 -4 It was Ωcm.
[0048] <Production Example 8> Copper filler was added to a thermoplastic resin based on SIS (styrene-isoprene-styrene) elastomer using a three-roll mill, and then tackifier, softener, antioxidant, and solvent were added and mixed for 1 hour. The resulting mixture was printed on a Kapton substrate to obtain an electrode sheet with a thickness of 350 μm. The volume resistivity of the electrode part was 2×10 -4 It was Ωcm.
[0049] <Production Example 9> Zinc filler was added to a thermoplastic resin based on SIS (styrene-isoprene-styrene) elastomer using a three-roll mill, and then tackifier, softener, antioxidant, and solvent were added and mixed for 1 hour. The resulting mixture was printed on a Kapton substrate to obtain an electrode sheet with a thickness of 200 μm. The volume resistivity of the electrode part was 1×10 -1 It was Ωcm.
[0050] <Production Example 10> Aluminum filler was added to a thermoplastic resin based on SEPS (styrene-ethylene-propylene-styrene) elastomer using a three-roll mill, and then tackifier, softener, antioxidant, and solvent were added and mixed for 1 hour. The resulting mixture was printed on a PEN substrate to obtain an electrode sheet with a thickness of 200 μm. The volume resistivity of the electrode part was 1×10 -2 It was Ωcm.
[0051] [Preparation of conductive gel layer] <Comparative Manufacturing Example 1> An electrode sheet with ionic conductivity was obtained by laminating an ionic conductive gel made by mixing a polymer (Poly(styrene-b-ethylene oxide-b-styrene): PS-PEO-PS) and an ionic liquid on an aluminum foil. The ionic conductivity of the electrode site was 4×10 -2 It was Scm.
[0052] <Comparative Manufacturing Example 2> An electrode sheet with ionic conductivity was obtained by laminating an ionic conductive gel made by mixing a polymer (Poly(styrene-b-ethylene oxide-b-styrene): PS-PEO-PS) and an ionic liquid on a copper foil. The ionic conductivity of the electrode site was 4×10 -2 It was Scm.
[0053] Next, the electrode sheet obtained in Production Example 1 was used to carry out the following tests.
[0054] 1. Measurement of volume resistivity and ionic conductivity The electrode sheet containing the film substrate prepared in Production Example 1 was cut to 1.5 cm x 3 cm, and the volume resistivity of the electrode portion was measured using a low resistivity meter (Mitsubishi Chemical Analytech Co., Ltd.: Loresta GX MCP-T700). Three measurements were taken, and the average value was used as the measured value. The ion conductivity of the ion gel electrode prepared in Comparative Production Example 1 was measured using an impedance analyzer (SI1260A / 1296A manufactured by Solartron Corporation). The measurement was carried out three times, and the average value was taken as the measured value.
[0055] 2. Measurement of Adhesion Strength The adhesive strength was evaluated using a tensile tester EX-SX manufactured by Shimadzu Corporation. The conductive hot melt adhesive layer with a thickness of 200 μm formed on the Kapton film substrate obtained in Production Example 1 was cut into a sheet with a width of 25 mm, and the conductive hot melt layer side was attached to the surface of a 7 cm x 7 cm concrete structure that had been surface-polished with a grinder. Furthermore, a plate heated to 200°C was pressed against the substrate for 1 minute to adhere to the concrete. After heating, the sample was left for 24 hours until it returned to room temperature, and this was used as the measurement sample. The adhesive strength was evaluated from the load when the edge of the sheet was peeled off at an angle of 90 degrees at a speed of 50 mm / min. Adhesive strength of 10 N or more was marked as ○, and otherwise marked as ×. Grinder used: Monotaro Slim Disc Grinder (MRO-100DG)
[0056] Tests for Production Examples 2 to 10 and Comparative Production Example 1 were carried out in the same manner as in the test for Production Example 1. The results are shown in Table 1.
[0057] <Example 1> 3.Measurement of electromotive force The electromotive force or potential difference was measured in an indoor environment at a temperature of 20°C and humidity of 50% using a digital multimeter 34465A manufactured by Keysight Technologies. Electrode sheet A, which is a laminate of a 200μm thick adhesive conductive hot melt layer and a Kapton film substrate obtained in Manufacturing Example 1, and electrode sheet B, which is a laminate of a 100μm thick adhesive conductive hot melt layer and a PEN film substrate obtained in Manufacturing Example 2, were cut to a width of 1cm and a length of 4cm, and attached to the surface of a 7cm x 7cm concrete structure that had been surface-polished with a grinder, with the adhesive strength of the electrode sheets so that they were parallel to each other with a 2cm gap between them, to form a power generation device before thermal bonding. The electromotive force or potential difference obtained between the two electrode sheets was measured in absolute value terms, and was evaluated on a four-point scale according to the following. 1: The potential difference is less than 50mV 2: The potential difference is 50 mV or more but less than 200 mV 3: Potential difference is 200mV or more but less than 500mV 4: Potential difference is 500mV or more Furthermore, a plate heated to 200°C was pressed onto the substrate for one minute to adhere it to the concrete. After heating, the device was left to cool to room temperature for 24 hours to form a power generating device after thermal adhesion, and the electromotive force or potential difference obtained between the two electrode sheets was measured in the same way and rated on a three-point scale. If the change in potential within one week during the potential measurement was within 100mV, it was marked as ◯, otherwise it was marked as ×.
[0058] <Examples 2 to 11, Comparative Examples 1 to 2> Tests for Examples 2 to 11 and Comparative Examples 1 and 2 were carried out in the same manner as in Example 1, except that the electrode sheet was changed as shown in Table 2. The results are shown in Table 2.
[0059] The abbreviations for the conductive tapes listed in Table 2 are as follows. <Conductive tape> Conductive tape 1: Mitsui Sumitomo Metal Mining Copper Co., Ltd. Product name: ZAP tape Conductive tape 2: 3M Japan Ltd. Product name: Conductive copper foil tape 1245 Conductive tape 3: 3M Japan Ltd. Product name: Lead foil tape 420 Conductive tape 4: 3M Japan Ltd. Product name: Conductive aluminum foil tape AL-25BT
[0060] [Table 1]
[0061] [Table 2] [Explanation of symbols]
[0062] 1 Concrete or electrolyte structure 2 Electrode sheet 3. Wiring 10. Electromotive force extractor or potential difference meter
Claims
1. A power generation device including a structure having an electrolyte and a pair of electrodes disposed on the structure, the structure having an electrolyte is concrete or mortar, At least one of the pair of electrodes has a conductive hot melt adhesive layer containing a conductive filler and a thermoplastic resin (excluding those having one or more gel layers constituted by a hydrogel layer or an ion gel layer); A power generating device having the conductive hot melt adhesive layer disposed on a surface of a structure.
2. 2. The power generating device according to claim 1, wherein the conductive filler comprises at least one selected from the group consisting of graphite, carbon black, carbon nanotubes, graphene, graphene oxide, silver, copper, tin, zinc, zinc oxide, nickel, manganese, aluminum, and ITO.
3. The power generating device according to claim 1 or 2, wherein the conductive filler comprises graphite, carbon black, carbon nanotubes, graphene, or graphene oxide.
4. The power generating device according to claim 1 , wherein the thermoplastic resin includes a thermoplastic elastomer.
5. A power generation device described in any one of claims 1 to 4, wherein at least one of the pair of electrodes is an electrode sheet in which the conductive hot melt adhesive layer is arranged in a pattern on a sheet-like substrate.
6. A method for manufacturing a power generating device including a structure having an electrolyte and a pair of electrodes disposed on the structure, the method comprising the steps of: the structure having an electrolyte is concrete or mortar, A method for manufacturing a power generation device, characterized in that at least one of a pair of electrodes has a conductive hot melt adhesive layer containing a conductive filler and a thermoplastic resin (excluding those having one or more gel layers composed of a hydrogel layer or an ion gel layer), and the method includes a step of adhering the conductive hot melt adhesive layer to a surface of a structure.
7. 7. The method for manufacturing a power generating device according to claim 6, wherein the step of adhering the conductive hot melt adhesive layer to the surface of the structure includes a step of heating the conductive hot melt adhesive layer to adhere to the surface of the structure.
Citation Information
Patent Citations
Pole piece structure of ultrathin battery and ultrathin battery
CN211578910U
Adhesive agent with anisotropic conductivity
JP2003317826A
Adhesive gel sheet, electrode and method of producing adhesive gel sheet
JP2015003977A
Novel separator for electrochemical systems
JP2015519686A
Hot-melt adhesive composition and laminate
JP2018135422A
